Neurogenic Thoracic Outlet Syndrome in Athletes — Nonsurgical Treatment Options. Issue 6 (June 2021) - Warrick, Alexandra; Davis, Brian
Abstract : Abstract: Neurogenic thoracic outlet syndrome (NTOS) is an etiologically and clinically diverse disorder caused by compression of the brachial plexus traversing the thoracic outlet. Athletes who perform repetitive overhead activities are at risk of developing NTOS with sport-specific symptoms. This article reviews the controversial NTOS nomenclature, common sites of anatomic compression, and red flag symptoms that require immediate intervention. It also reviews the congenital, traumatic, and functional etiologies of NTOS, with a discussion of the differential diagnosis, diagnostic criteria, and workup for NTOS. Nonsurgical treatment is highlighted with an emphasis on thoracic outlet syndrome-specific physical therapy and updates on injection options and ultrasound guided hydrodissection. This article compares nonsurgical versus surgical functional outcome data with an emphasis on athletes with NTOS. Functional assessment tools and performance metrics for athletes are reviewed, as well as return to sport considerations.